Theoretical models for chronotherapy: Periodic perturbations in funnel chaos type - Juvencio Alberto Betancourt-Mar; José Manuel Nieto-Villar (Mathematical Biosciences and Engineering)
In this work, the Räossler system is used as a model for chrono-therapy. We applied a periodic perturbation to the y variable to take theRössler system from a chaotic behavior to a simple periodic one, varying theperiod and amplitude of forcing. Two types of chaos were considered, spiraland funnel chaos. As a result, the periodical windows reduced their areas as thefunnel chaos character increased in the system. Funnel chaos, in this chrono-therapy model, could be considered as a later state of a dynamical disease,more irregular and difficult to suppress.